Species-Level Analysis of Human Gut Microbiota With Metataxonomics - Jing Yang (Frontiers in Microbiology, 2020)
The current understanding of human gut microbial community is mainly limited to taxonomic features at the genus level. Here, we examined the human gut microbial community at the species level by metataxonomics. To achieve this purpose, a high-throughput approach involving operational phylogenetic unit analysis of the near full-length 16S ribosomal RNA (rRNA) gene sequence was used. A total of 1,235 species-level phylotypes (SLPs) were classified in the feces of 120 Chinese healthy individuals, including 461 previously classified species, 358 potentially new species, and 416 potentially new taxa, which were categorized into low, medium, and high prevalent bacteria groups based on their prevalence. Each individual harbored 186 ± 51 SLPs on average. There was no universal bacterial species shared by all the individuals. However, 90 ± 19 of 116 SLPs were shared in the high prevalent bacteria group. Thirty-two out of thirty-eight species in the high prevalent bacteria group detected in this study were also found in at least one previous study on human gut microbiota based on either culture-dependent or culture-independent approaches. Through compositional analysis, a hierarchical clustering of the prevalence and relative abundance of the 1,235 SLPs revealed two types of gut microbial communities, which were dominated by Prevotella copri and Bacteroides vulgatus, respectively. The type dominated by P. copri was more prevalent in northern China, while the B. vulgatus-dominant type was more prevalent in southern China. Therefore, P- and B-type gut microbial communities in China were proposed. It was found that 166 out of 461 known bacterial species have been previously reported as potential pathogens, and the individuals sampled for this study harbored 20 of these potential pathogenic species on average. The top two most abundant and prevalent potential pathogenic species were Klebsiella pneumoniae and Bacteroides fragilis.